Implementasi SAK EMKM dalam Penyajian Laporan Keuangan pada UMKM Bidang Industri Pangan - Fransiska Wahyu Lestari; Yohanes Suharsana; Devi Yani (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2022)
The purpose of this study was to determine whether the MSMEs of the Food Industry in East Hadimulyo, has implemented the FAS MSMEs. This research uses descriptive method, by looking at the elements presented in the financial statements in the MSMEs of Food Industry, East Hadimulyo and comparing them with the applicable the FAS MSMEs. And the result of this research is that the presentation of financial reports on MSMEs of Food Industry Sector, East Hadimulyo, has not implemented the FAS MSMEs. This is due to the lack of in-depth knowledge related to the preparation and presentation of financial statements.